Megaloblastic Anemia in Early Infancy (A Case Report) - Jamal, Dr. Sara; Imtiaz, Dr. Amna; Naseem, Dr.Lubna (International Journal of Pathology, 2018)
Congenital megaloblastic anemia is a rare hematological condition of early infancy and so far few cases have been reported. Infants born to severely B12 deficient mothers develop megaloblastic anemia at 3 to 6 months of age since they are born with low stores of B12 and are then fed breast milk of low cobalamin content. Mothers of such infants are either vegetarians or have unrecognized maternal pernicious anemia. Megaloblastic anemia developing within few weeks of birth is due to congenital transcobalamin II deficiency or abnormality. Transcobalamin II is responsible for the transport of cobalamin from gut to body tissues. Megaloblastic Anemia can also occur due to functional defect in either mitochondrial methyl malonyl COA enzyme or its co-factor ado cobalamin.Here we report a case of 3months old female child who presented with complaints of bruises, fever, cough and progressive pallor. Her complete blood picture showed bicytopenia (decreased Hemoglobin and platelets) with macro ovalocytes and anisocytosis on peripheral blood smear and low retics count. Bone marrow showed hyper cellularity and megaloblastic erythroid series with no atypical cells. Iron stores were markedly increased and few siderocytes were seen. Hence diagnosis of megaloblastic anemia was made. Since patient was already transfused, her folate and Vitamin B12 levels were not done. However, her maternal Vitamin B12 levels were found out to be markedly low. Unfortunately, before start of specific treatment, patient expired. This case is described due to its rarity and importance of early diagnosis and immediate intervention